(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to analyze the characteristics of drug formulary utilization at Le Van Thinh Hospital (LVTH) during the period from 2018 to 2023. Methods: The characteristics of the drug formulary were examined based on active ingredient composition, drug origin, manufacturing country, route of administration, and pharmacological action groups. Data were analyzed by the number of drugs in each characteristic group, both annually and over the total six-year period (2018–2023). The data were compiled, processed, and analyzed using Microsoft Excel. Results: From 2018 to 2023, LVTH utilized 2,746 different pharmaceuticals, covering all 26 drug groups listed for health insurance reimbursement. The annual number of drugs ranged from 1,097 to 1,313. Among the total of 2,746 drug types, single-component drugs accounted for 82.0%, while generic drugs represented 86.5%. Vietnamese-manufactured drugs comprised 52.2%, and oral and injectable drugs made up 68.8% and 22.6%, respectively. The five most common drug groups included cardiovascular drugs (28.4%), antiparasitic and anti-infective drugs (17.1%), hormones and drugs acting on the endocrine system (7.0%), gastrointestinal drugs (6.9%), and drugs affecting blood (6.4%). Conclusion: This study has outlined several key characteristics of the drug formulary utilized at Le Van Thinh Hospital from 2018 to 2023. The findings provide important insights to assist the Hospital’s Drug and Therapeutics Committee in evaluating and adjusting LVTH’s drug formulary to better align with the actual needs of the hospital and to comply with national drug policy requirements.